Malignant tumor of the peripheral nerve sheath in a left Whippet canine kidney - Freitas, Rosemar de Almeida; Filho, Mário dos Santos; de Campos, Simone Neves; Corrêa, Luciana Martins; de Carvalho, Wagner Tavares Silveira; de Moraes, Matheus Abreu; Gomes, Viviane Horta; Netto, Carlos Eduardo Cotias (Acta Scientiae Veterinariae, 2020)
Background: Malignant tumors of the peripheral nerve sheath (MTPNS`s) are considered rare tumors that can affect soft tissues. In dogs, the occurrence is more common in the nerves of the brachial plexus, but they can affect the lumbosacral plexus and cranial nerves. Rarely, they can affect spinal nerves and nerve roots and the urinary tract, especially in kidneys. The present report aims to describe a clinical case of a 10-year-old sterilized female whippet, who had a history of persistent hematuria for months, with subsequent diagnosis of MTPNS as the cause of hematuria. Case: The patient came for evaluation with a history of persistent hematuria. Evaluation of abnormal elements and sedimentation, showed the description of numerous red blood cells and the presence of proteinuria. The abdominal ultrasound revealed a left kidney with enlarged dimensions, irregular contour, loss of corticomedullary definition. The urinary vesicle showed an increase in cellularity. On physical examination, the patient had vital parameters within the normal range. A Snap 4DX® Plus exam was requested, which showed a reaction for Dirofilaria immitis. With this result, it was initially suspected that renal vasculitis. After starting the treatment, the patient started to present normal colored urine. However, after the end of this period, the patient returned to hematuria. After six months of treatment and without justification for the permanence of hematuria, urethrocystoscopy was indicated, which revealed a urinary vesicle with a hemorrhagic focus. A urinary bladder wall biopsy was performed, which showed no changes. Four months after the urethrocystoscopic exam, the patient had her first azotemic crisis. This time that the left renal neoformation observed on ultrasound examination. With the discovery of the origin of the problem, a therapeutic approach could be instituted, consisting of the left nephrectomy. The histopathological analysis showed malignant spindle cell neoplasia. Immunohistochemical analysis in peroxidase revealed positivity for the markers, concluding the diagnosis as a tumor of the peripheral nerve sheath. Seven months after surgery, a new ultrasound examination of the abdominal region, as well as tests for the assessment of renal function, all of which were within normal parameters. Discussion: Most of the MTPNS originate in the peripheral nerves and in the cranial nerve sheath, but it can rarely originate in the abdominal cavity, as in the case reported here, in which the origin was renal. Such neoplasms are not common in dogs, with an incidence of 0.5%. The age of the affected dogs is, on average, nine years for the appearance of the neoplasia, with females with the highest frequency of occurrence. Both data corroborate the patient’s age at the time of diagnosis. This is a tumor that is considered to be highly malignant and progressive, which did not occur in the patient in question, since she had a history of persistent hematuria for a long period, with no manifestation of the presence of the tumor on imaging. Still regarding the clinical manifestation of the patient’s persistent hematuria, the same occurrence can be observed in a human patient who also reported a history of persistent hematuria and, like the patient in the report, not associated with any other clinical signs. It is important to differentiate this type of neoplasia from the others, because in many cases, the histological patterns are similar, making the performance of immunohistochemistry essential for the diagnosis. Renal MTPNS is rare in humans, and in dogs it is no different. This fact makes it difficult to describe the prognosis. Thus, efforts should be considered for the early diagnosis of peripheral nerve neoplasms, in view of their low response to available halopathic treatments and taking into account the rare aspect and evolution of this disease.